Study of cod reduction by anaerobic digestion using mixed culture from industrial waste - Hwa, Ooi Kuan (2010)
The study of COD reduction using mixed culture from paper mill wastewater has been investigated. The treatment is using anaerobic digestion. Two Litre Scott bottle was used as digester. The gas production from the digestion process was also studied. The methodology consists of 2 main parts. The first part is the culturing procedure, in which the mixed culture was prepared by culturing the microorganisms from the wastewater sample that was collected from the treatment plant of Pascorp Paper Industries in Bentong, Pahang. The second part is treatment of synthetic waste using anaerobic digestion. Four digesters with glucose concentrations of 1 to 4 g/L were prepared. The digestion process was initiated by mixing the mixed culture with the glucose. The digesters were closed and the experiment was run for 5 days. Sample was taken every day from each digester to check the COD value and turbidity. The gas production rate was also measured using the water displacement unit. The results show that COD reduction of over 90% was achieved after 5 days of digestion in all concentrations of glucose. The gas production rate was not consistent with respect to the glucose concentration and time of digestion but the average gas production rate shows that the higher the glucose concentration the higher the gas production. In conclusion, the mixed culture collected from wastewater of paper mill has proved its ability to efficiently reduce the COD concentration. The average gas production rate shows a higher rate at digestion of higher glucose concentration.